1996
DOI: 10.1046/j.1471-4159.1996.66010394.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Role of Conserved Serine Residues in the Long Form of the Rat D2 Dopamine Receptor Using Site‐Directed Mutagenesis

Abstract: Three serine residues (Ser193, Ser194, Ser197) in the fifth transmembrane‐spanning region of the D2 dopamine receptor have been mutated separately to alanine and the effects of the mutations determined in ligand‐binding experiments with [3H]spiperone. For many antagonists the mutations had little effect, showing that the overall conformation of the mutant receptors was similar to that of the native, although there were effects on the binding of certain antagonists. The effect of the mutations on agonist bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 7 publications
7
57
1
Order By: Relevance
“…Mutation of serine 194 in the dopamine D2 receptor is reported to have little or no effect on spiperone binding. 18 The S194A mutated receptor, stably expressed in transfected C6 cells, was unable to inhibit hormone-stimulated elevation of cyclic AMP accumulation in response to dopamine stimulation. 18 While we find that mutation of serine 194 to alanine substantially reduces the signaling capacity of the dopamine D2 receptor, we still detect a modest ability of the D2R194A mutant receptor to modulate cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mutation of serine 194 in the dopamine D2 receptor is reported to have little or no effect on spiperone binding. 18 The S194A mutated receptor, stably expressed in transfected C6 cells, was unable to inhibit hormone-stimulated elevation of cyclic AMP accumulation in response to dopamine stimulation. 18 While we find that mutation of serine 194 to alanine substantially reduces the signaling capacity of the dopamine D2 receptor, we still detect a modest ability of the D2R194A mutant receptor to modulate cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…18 The S194A mutated receptor, stably expressed in transfected C6 cells, was unable to inhibit hormone-stimulated elevation of cyclic AMP accumulation in response to dopamine stimulation. 18 While we find that mutation of serine 194 to alanine substantially reduces the signaling capacity of the dopamine D2 receptor, we still detect a modest ability of the D2R194A mutant receptor to modulate cAMP levels. Since preliminary binding data suggested that there is not much difference in the ability of the two mutant D2R receptors to bind [ 3 H]spiperone, we have examined more fully the ability of the D2R80A mutant receptor to bind ligand and to function as a PET reporter gene in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has attracted much attention as a potential target for the design of novel antipsychotic drugs with reduced motor side effects (Sokoloff and Schwartz, 1995). The D 3 dopamine receptor is related structurally and functionally to the D 2 dopamine receptor, but a notable difference between the two is the markedly higher affinity of the D 3 receptor for certain agonists, e.g., dopamine, quinpirole, and 7-hydroxydipropylaminotetralin (7-OH-DPAT) (Neve and Neve, 1997).Agonist interaction with the D 2 dopamine receptor has been studied extensively using mutagenesis and modelling approaches, and this has identified three serine residues (Ser 193 , Ser 194 , and Ser 197 ) that are important for interaction of the catechol hydroxyl groups of dopamine and other catecholcontaining agonists with the receptor (Cox et al, 1992;Mansour et al, 1992;Woodward et al, 1996). The higher affinities of certain agonists for the D 3 receptor as compared with the D 2 receptor may be due to stronger interactions with the corresponding serine residues (Ser 192 , Ser 193 , and Ser 196 ), but the role of these serine residues has not been studied for the D 3 receptor.…”
mentioning
confidence: 99%